High-Fat Diet During Mouse Pregnancy and Lactation Targets GIP-Regulated Metabolic Pathways in Adult Male Offspring - Kruse, Michael; Keyhani-Nejad, Farnaz; Isken, Frank; Nitz, Barbara; Kretschmer, Anja; Reischl, Eva; de las Heras Gala, Tonia; Osterhoff, Martin A.; Grallert, Harald; Pfeiffer, Andreas F.H. (Diabetes (New York, N.Y.), 2016)
Maternal obesity is a worldwide problem associated with increased risk of metabolic diseases in the offspring. Genetic deletion of the gastric inhibitory polypeptide (GIP) receptor (GIPR) prevents high-fat diet (HFD)–induced obesity in mice due to specific changes in energy and fat cell metabolism. We investigated whether GIP-associated pathways may be targeted by fetal programming and mimicked the situation by exposing pregnant mice to control or HFD during pregnancy (intrauterine [IU]) and lactation (L). Male wild-type (WT) and Gipr−/− offspring received control chow until 25 weeks of age followed by 20 weeks of HFD. Gipr−/− offspring of mice exposed to HFD during IU/L became insulin resistant and obese and exhibited increased adipose tissue inflammation and decreased peripheral tissue substrate utilization after being reintroduced to HFD, similar to WT mice on regular chow during IU/L. They showed decreased hypothalamic insulin sensitivity compared with Gipr−/− mice on control diet during IU/L. DNA methylation analysis revealed increased methylation of CpG dinucleotides and differential transcription factor binding of promoter regions of genes involved in lipid oxidation in the muscle of Gipr−/− offspring on HFD during IU/L, which were inversely correlated with gene expression levels. Our data identify GIP-regulated metabolic pathways that are targeted by fetal programming.